Determinación de las complicaciones postquirúrgicas de los pacientes tiroidectomizados por patología tiroidea en el servicio de cirugía oncológica en el Hospital Manual Ygnacio Monteros en el periodo 2012-2013 - Neciosup Carranza, Mariana Alejandra (2015)
The postoperations complications are a dare to the professionals on the surgical ambit, it is the reason around the world is following to realize studies which are on the search of protocols for a better manage of the post operations complications, and opportune detection of them, today we can see the demand of interventions in the cancer of thyroidectomy services and its complications, that is why that this investigation pretends to determine the post surgeries complications on the thyroidectomies patients, realized on Manuel Ygnacio Monteros Hospital in two years 2012-2013 on Loja city. The study was of transversal type, quantitative, qualitative, and descriptive; the same which had been realized on that Hospital, the sample had 197 patients, which presents post surgeries complications 35 in total. In the base´s recollections has used a format where includes all the data for the future tabulation, which the results were presented on draws and graphics realized on Microsoft Office Excel 2010. On the thyroidectomies patients and evidenced that in the 2012 year, and presented hypocalcemia (60%), dysphonia.(30%), and vocal cord paralysis (10%); in the 2013 year predominated hypocalcemia (48%), dysphonia.(32%), accumulation of blood (8%), and vocal cord paralysis (4%). The population more affected was the female kind and the ages between 40-49 and 50-59 years. Another way, it realized and educative talk to the medicine´s rotaries internals on 09 January 2015.The present study was conducted under the direction of Dr. Nelson Fernando Samaniego Idrovo during the period February 12, 2014 until January 15, 2015.